City branding in polycentric urban regions: identification, profiling and transformation in the Randstad and Rhine-Ruhr. Issue 11 (1st November 2016) - Goess, Simon; de Jong, Martin; Meijers, Evert
ABSTRACT: In polycentric urban regions several distinct cities, none of which is dominant, cooperate and compete with each other to attract inhabitants and firms. In such settings city branding strategies do not solely affect one city, but the entire region. We examined how city branding in the face of ecological modernization, that is, delivering higher added economic value, while lowering environmental impacts, is playing out in the Dutch Randstad and the German Rhine-Ruhr. Our findings show that regional identity formation occurs at the sub-polycentric urban region level, coinciding more with (historical) economic profiles than with planning imaginaries. The Dutch cities profile themselves more along the lines of ecological modernization than their German counterparts. Differences between subregions within each polycentric urban region are also noticeable, where more industrialized regions, such as the Ruhr or southern Randstad focus on 'green', 'liveable' and 'knowledge-oriented', while cities with stronger knowledge-intensive sectors portray themselves as 'smart' or 'sustainable'. Cities generally substantiate their profiles through projects, but a significant gap persists between reality and aspirations for improved environmental conditions. This is especially true for the Dutch cities, where many claims, but little visible action can be observed.